Practicing software engineering in the 21st century - Peckham, Joan 1948-; Lloyd, Scott J. (IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2003)
"This book addresses the tools and techniques utilized when developing and implementing software engineering practices into computer systems"--Provided by publisher